Relationship between dietary intake and growth and development in Chinese pupils - Fang, Wen; Fu, Ye; Li, Qin; Cheng, Menghan; Zhang, Miao; Lu, Yu (Frontiers in Public Health, 2025)
BackgroundA nutritional diet is essential for children’s growth and development. This study aimed to investigate the relationship between dietary intake and growth and development of pupils to provide more specific nutritional recommendations for their healthy growth.MethodsThis cross-sectional study included 592 pupils, and standardized questionnaires were used to collect information on students’ sociodemographic characteristics, lifestyle habits and dietary intake. Growth and development assessment indicators were measured according to standard protocols. The multivariate generalized linear regression models adjusted for covariates were used to investigate the association between dietary intake and growth and development of pupils.ResultsThe generalized linear regression model showed that standing long jump of all pupils (β = −6.735, 95% CI: −12.064, −1.406) and body fat rate (β = −2.650, 95% CI: −4.794, −0.507), fat weight (β = −1.283, 95% CI: −2.286, −0.280) and chest circumference (β = −1.456, 95% CI: −2.789, −0.123) of boys were negatively correlated with dietary diversity score. Among all pupils, meat intake was positively correlated with chest circumference (β = 0.420, 95% CI: 0.119, 0.721) and negatively correlated with standing long jump(β = −1.991, 95% CI: −3.902, −0.080); milk intake was positively correlated with waist circumference (β = 0.470, 95% CI: 0.007, 0.932); soybean intake was negatively correlated with body fat rate (β = −0.583, 95% CI: −1.125, −0.042), fat weight (β = −0.262, 95% CI: −0.517, −0.006), and waist circumference (β = −0.607, 95% CI: −1.050, −0.164); and vegetable intake was negatively correlated with height (β = −0.290, 95% CI: −0.496, −0.084), and positively correlated with stature-sitting height index and waist circumference (p < 0.05). Certain associations retained significance even after stratified analysis based on gender and frequency of dietary intake.ConclusionDietary diversity score and their respective food groups such as meat, milk, coarse grain, soybean and vegetable will impact growth and development indicators, requiring purposefully controlled dietary intake.